2002
DOI: 10.1159/000058447
|View full text |Cite
|
Sign up to set email alerts
|

Arteriosclerosis of Penile Arteries: Histological Findings and Their Significance in the Treatment of Erectile Dysfunction

Abstract: Objectives: In this pathomorphological study, location, distribution, and degree of arteriosclerotic stenoses in penile arteries from unselected cadavers are investigated. The findings are discussed in the context of penile revascularization and may explain the poor results of this form of surgery in older patients with general arteriosclerosis. Materials and Methods: 120 penile specimens from 120 cadavers were examined histologically after van Gieson staining. Transverse sections were performed at the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…In addition to this aging-related fibrosis of the arterial media [3][4][5][6], it is well documented that similar fibrotic changes occur within the penile corporal sinusoids [37]. The corporal tissue comprises primarily of a syncytium of vascular SMC with an endothelium lining, which is biologically and physiologically indistinguishable from the one present in the media and intima of the vascular tree and may be considered a highly evolved extension of these arterial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this aging-related fibrosis of the arterial media [3][4][5][6], it is well documented that similar fibrotic changes occur within the penile corporal sinusoids [37]. The corporal tissue comprises primarily of a syncytium of vascular SMC with an endothelium lining, which is biologically and physiologically indistinguishable from the one present in the media and intima of the vascular tree and may be considered a highly evolved extension of these arterial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mersdorf et al [18] found varying degrees of pathologic changes in the right and left corpora cavernosa in approximately 17% of their patients. Another study showed that atherosclerotic lesions were localized more often in the distal part of the penile arteries than in the proximal part [24].…”
Section: Surplus Clinical Valuementioning
confidence: 99%
“…, 1992). Arteriogenic ED results from haemodynamic impairment and chronic exposure of erectile tissue to ischaemia and hypoxia, nutrient deficiency and a lack of metabolic waste clearance (Grein & Schubert, 2002; Siroky & Azadzoi, 2003; Azadzoi et al. , 2005).…”
Section: Introductionmentioning
confidence: 99%